2001
DOI: 10.1152/jappl.2001.90.5.1887
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen measurements in brain stem slices exposed to normobaric hyperoxia and hyperbaric oxygen

Abstract: We previously reported (J Appl Physiol 89: 807-822, 2000) that < or =10 min of hyperbaric oxygen (HBO(2); < or = 2,468 Torr) stimulates solitary complex neurons. To better define the hyperoxic stimulus, we measured PO(2) in the solitary complex of 300-microm-thick rat medullary slices, using polarographic carbon fiber microelectrodes, during perfusion with media having PO(2) values ranging from 156 to 2,468 Torr. Under control conditions, slices equilibrated with 95% O(2) at barometric pressure of 1 atmosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 46 publications
7
91
0
Order By: Relevance
“…Our data shows that normobaric hyperoxygenated ASCF (95% O2/5% CO 2 at normal atmospheric pressure) at flow rate 2 ml/min provides constant normoxic conditions at 100-150 μm depth of slice. These results are close to previous studies investigating the oxygen profile in the brain slice tissue under various perfusion rate and oxygen concentrations [7,13]. In contrast, in the conditions of the absence of medium flow in the recording chamber we observed progressive reduction in the pO 2 as well as decrease in the power of 4-AP-induced synchronous neuronal activity.…”
Section: Discussionsupporting
confidence: 91%
“…Our data shows that normobaric hyperoxygenated ASCF (95% O2/5% CO 2 at normal atmospheric pressure) at flow rate 2 ml/min provides constant normoxic conditions at 100-150 μm depth of slice. These results are close to previous studies investigating the oxygen profile in the brain slice tissue under various perfusion rate and oxygen concentrations [7,13]. In contrast, in the conditions of the absence of medium flow in the recording chamber we observed progressive reduction in the pO 2 as well as decrease in the power of 4-AP-induced synchronous neuronal activity.…”
Section: Discussionsupporting
confidence: 91%
“…Neural tissue O 2 -depth profiles have been previously reported in vivo (for summary see Garcia 3rd et al 2010), in situ in the working heart-brain stem preparation (Wilson et al 2001), as well as in vitro in both isolated brain stem-spinal cord preparations (Brockhaus et al 1993;Okada et al 1993) and brain slices (Bingmann and Kolde 1982;Garcia 3rd et al 2010;Mulkey et al 2001). Several factors influence the degree of in vitro tissue oxygenation within a brain slice.…”
Section: In Vitro Tissue Oxygenationmentioning
confidence: 97%
“…Although only a handful of brain slice studies have shown that neuronal activity is affected throughout a broad range of O 2 tensions outside of hypoxia (0% O 2 ) and the conventional control condition (95% O 2 ), these studies have shown that graded changes in O 2 , and not only hypoxia, can influence biochemical activity (D'Agostino 2007;Fowler 1993) and excitability of neurons within local networks (Fowler 1993;Garcia 3rd et al 2010;Hoffmann et al 2006;Mulkey et al 2001). Similarly, in invertebrate systems, small changes in oxygenation also have been shown to influence network activity (Clemens et al 2001).…”
Section: In Vitro Tissue Oxygenationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, hyperoxic gas mixtures are routinely used for chemical denervation of peripheral O 2 receptors in in-vivo studies of respiratory control. The response mechanisms under hyperoxic inhalation conditions are commonly considered to be regulated by oxygen-chemosensitive neurons of the central nerve system, which are distributed throughout the brain stem from the thalamus to the medulla (Neubauer and Sunderram, 2004;Dean et al, 2003Dean et al, , 2004Mulkey et al, 2001). Therefore, the higher response level of P t O 2 during 100% O 2 inhalation in AGS compared to rat is accounted by the regulation mechanism controlled by oxygen-chemosensitive neurons of the central nerve system.…”
Section: Hyperoxic Response and Brain Tissue Oxygenationmentioning
confidence: 99%